A Comparison of Quality of life in Patients of Mandibular Condyles Fractures Treated with Open Versus Close Reduction - Nasir Abbas, Asif Nazir, Fahad Khaliq, Tanveer Ahmed Khan, Muhammad Fishan, Aysha Shaukat, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The notion of quality of life pertains to the subjective assessment made by people on their overall well-being, taking into account their cultural and value orientations, as well as their goals, expectations, standards, and concerns. The notion of quality of life (QoL) within the medical field is often denoted as Health-Related Quality of Life (HR-QoL) or subjective health status. The primary objective of research on quality of life (QoL) is to evaluate the influence of sickness, disease, and their corresponding therapies on the holistic welfare of individuals. Objectives: The objectives of the study are to compare quality of life in patients of mandibular condylar fractures treated with open versus close reduction. Method: A total of 84 individuals diagnosed with subcondylar fractures of the mandible were subjected to evaluation. All fractures seen in the study exhibited displacement, either in the form of angulation ranging from 10° to 35° or a shortening of the ascending ramus by more than 2 mm. A comprehensive assessment, including both clinical and radiographic examination, was conducted at the 6-month mark after the occurrence of the trauma. The clinical characteristics assessed in this study included oral pain, difficulty in chewing, discomfort, cosmetic deformity, impact on daily routine, and symptoms of sadness. Results: The findings of the study indicate a statistically significant difference between the two groups, with a p-value of less than 0.05. The findings suggest that open reduction had superior outcomes compared to closed reduction in terms of alleviating oral pain, enhancing chewing ability, reducing discomfort, addressing cosmetic deformities, minimising disruptions to daily activities, and mitigating depressive symptoms. Conclusion: The study has determined that open therapy yields a better improvement in quality of life compared to closed treatments, and these differences are statistically significant. Keyword: Mandibular condylar fracture, open reduction, closed reduction, Quality of life